2021
DOI: 10.1302/2058-5241.6.200074
|View full text |Cite
|
Sign up to set email alerts
|

Traditional versus congruent-arc Latarjet anatomic and biomechanical perspective

Abstract: The congruent-arc Latarjet (CAL) allows reconstruction of a greater percentage of glenoid bone deficit because the inferior surface of the coracoid is wider than the lateral edge of the coracoid used with the traditional Latarjet (TL). Biomechanical studies have shown higher initial fixation strength between the graft and the glenoid with the TL. In the TL, the undersurface of the coracoid, which is wider than the medial edge used with the CAL, remains in contact with the anterior edge of the glenoid, increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Latarjet is one of the most widely used surgical procedures for treating significant bone defects of the glenoid surface and failed Bankart repairs [2 4] . Although the TL procedure is effective for the management of recurrent anterior shoulder instability, it is not without complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latarjet is one of the most widely used surgical procedures for treating significant bone defects of the glenoid surface and failed Bankart repairs [2 4] . Although the TL procedure is effective for the management of recurrent anterior shoulder instability, it is not without complications.…”
Section: Discussionmentioning
confidence: 99%
“…The Latarjet procedure, also known as the coracoid process transfer, is one of the most performed and reliable procedures for treating recurrent anterior shoulder instability in patients with a significant bone defect of the glenoid surface [1 – 4] . In the traditional Latarjet (TL) procedure, the inferior surface of the coracoid process (CP) is transferred with the conjoint tendon to the anterior glenoid rim.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the bone distance around the screw has been associated with tolerance of screw-positioning error in Latarjet. 2 Attributing to the minimum coracoid bone graft length for safe screw insertion and the maximum osteotomy length that varies among individuals, preoperatively predicting SM is advocated for an efficient shoulder surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Calvo et al reported 11.8% of cases that remained off-track after undergoing a Latarjet procedure and they had a significantly higher rate of failure than those that converted to ‘on-track’ ( 12 ). In this clinical setting, some authors have suggested the congruent-arc technique as it provides approximately 5 mm more bone augmentation ( 13 ), while others might consider a better option addressing the Hill–Sachs lesion by adding a remplissage to the Latarjet procedure ( 14 ) or to increase the glenoid surface by means of a free bone graft ( 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%